PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR DI SMP NEGERI 4 BARAKA - Marsuki, M.Agil; Wahab, Abdul; Darmawangsa, Andi; Nurlaelah; Mustamin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of the "Snowball Throwing" learning model in improving student learning outcomes in the Islamic Religious Education subject for class VIII.A at SMP Negeri 4 Baraka, Enrekang Regency. The study was motivated by low student learning outcomes resulting from a learning process dominated by conventional methods, which led to a lack of student engagement and interest. The research employed Classroom Action Research (CAR) with a qualitative approach supported by quantitative data. It utilized the Kemmis and McTaggart model, comprising four stages—planning, action implementation, observation, and reflection—conducted over two cycles. The subjects of the study were 32 students from class VIII.A at SMP Negeri 4 Baraka, Enrekang Regency. Data collection techniques included observation, learning outcome tests, and documentation. The data were analyzed using both qualitative and quantitative descriptive analysis. The results indicate that the implementation of the Snowball Throwing learning model improved student learning outcomes. In the pre-cycle stage, the average learning outcome score was 54.37, with a mastery rate of 18.75%. Cycle I saw an improvement, with a mastery rate of 56.25%, though this did not yet meet the established success indicators. Subsequently, in Cycle II, student learning outcomes improved significantly, with an average score of 87.84 and a mastery rate reaching 87.5%. Teacher and student activities also increased; teacher activity rose from 72.9% in Cycle I to 90.3% in Cycle II, while student activity increased from 70% to 88.6%. Based on these results, it can be concluded that the implementation of the Snowball Throwing learning model is effective in improving student learning outcomes in the Islamic Religious Education subject for class VIII.A at SMP Negeri 4 Baraka, Enrekang Regency.